Characterisation of Langmuir-Blodgett films of new multinuclear copper and zinc phthalocyanines and their sensing properties to volatile organic vapours - (:unkn) unknown (ELSEVIER SCIENCE SA, 2007)
In the present article, we report about the characterisation and organic vapour sensing properties of Langmuir-Blodgett thin films of s-triazines bearing three oxygen-linked phthalocyanines incorporating Cu and Zn metals (CuPc and ZnPc). Surface pressure-area per molecule (pi-A) isotherms of CuPc and ZriPc monolayers at room temperature shows that stable monolayers of both materials are formed at the air-water interface. The LB film deposition processes of CuPc and ZnPc materials are characterized by UV-vis spectroscopy and a quartz crystal microbalance. The results indicate that high quality and uniform LB films can be prepared with the transfer ratio of over 0.95 and that the obtained LB films are significantly more sensitive to chloroform than other vapours. The response of the LB films is fast, large, and reversible. These newly synthesised CuPc and ZnPc materials are promising sensing materials in the development of room temperature volatile organic vapour sensing devices for chloroform vapour. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Langmuir-Blodgett film; phthalocyanine; vapour sensing; THIN-FILMS; LB FILM; SENSITIVE PROPERTIES; LEAD PHTHALOCYANINE; BIS-PHTHALOCYANINE; CHEMICAL SENSORS; SPUN FILMS; NO2; CONDUCTIVITY; SUBSTITUENTS